Chemical Control of Prolactin Secretion and It`s Effects on Pause Days, Egg Production and Steroid Hormone Concentration in Girirani Birds - Reddy, I.J.; David, C.G.; Raju, S.S. (International Journal of Poultry Science, 2006)
The objective of this study was aimed to improve egg production by decreasing the intersequence pause days between the sequences of egg lay in girirani birds through chemical control of prolactin by using bromocriptine (an anti prolactin chemical) through feed. At 12 weeks of age, forty two girirani birds were randomly divided into control (n=21) and treated (n=21) groups. Birds in the treated group were fed bromocriptine through feed @ 350μg/bird/day from 17-36 weeks of age and controls were fed the same ration without bromocriptine. Birds fed with bromocriptine through feed significantly (P< 0.01) reduced the prolactin concentration compared to control birds. Estradiol and progesterone were quantified in both the groups. Treated birds showed higher (P< 0.01) concentration of estradiol and progesterone concentration from 19th to 72 weeks of age with intermittent fluctuations. Egg production, pause days, and hormonal parameters were correlated between the two groups. Prolactin is negatively correlated with egg production (r = -0.89), estradiol (r = -0.59) and progesterone (r = -0.37) hormones and positively correlated with inter sequence pause days with concomitant decrease in egg production. Birds fed bromocriptine through feed showed significantly (P< 0.01) less pause days and more egg production. The results of this study showed that, controlling the prolactin secretion by chemical means resulted in 5.12% increase in egg production over control birds, further such an approach is more promising, practicable, economical without any traces of chemical in meat, egg and blood to improve egg production in backyard poultry farming. It is concluded that chemical control of prolactin plays a major role on pauses days , prolactin secretion and egg production in native breed of birds.